PESANTREN DAN PERILAKU HIDUP SEHAT ( STUDI TERHADAP PESANTREN NURUL YAQIN RINGAN-RINGAN ) - ZAINI, HASAN (State Institute for Islamic Studies Batusangkar, 2016)
Pesantren (Boarding School) have special characteristics in learning compared to other educational institutions, there is a boarding house to stay students. Nowadays the boarding life has less attention from stakeholders in the boarding school, it is seen from the boarding school’s atmosphere, such cleanliness which would cause various diseases for students. In this study, the researcher examined how is the school’s understanding to the cleanliness, however the classic books gave clear attention such fiqh thaharah (ablutions/sanitation). This study also predicted the way of traditional boarding school salafiah which represented by Pondok Pesantren Nurul Yaqin Ringan-Ringan in applying the hygiene of daily life.Keywords: Boarding School, Boarding House, School’s Atmosphere, Cleanliness.